USE OF SERIAL IMAGE MEDIA TO IMPROVE THE READING SKILLS OF UPT SMKN 8 MAKASSAR - Herawati, Arita; admin, admin (Publikasi dan UKI Press UKI Toraja., 2022)
This research aims to improve the reading skills of Class XI students at UPT SMKN 8 Makassar for the 2023/2024 academic year. The research method used is classroom action research (PTK). The sample consists of 1 class totaling 21 people. Classroom action research carried out in cycle I and cycle II using serial image media was proven to have improved students' reading abilities. This can be seen from the results of the percentage of student learning completeness in the Pre-cycle stage of 38%, Cycle I of 62%, and an increase in cycle II of 81%. So, it can be concluded that the use of serial image media can improve the reading skills of class XI students at UPT SMKN 8 Makassar.